2016
DOI: 10.1182/blood-2016-04-692665
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of platelet-mediated liver regeneration

Abstract: Platelets have multiple functions beyond their roles in thrombosis and hemostasis. Platelets support liver regeneration, which is required after partial hepatectomy and acute or chronic liver injury. Although it is widely assumed that platelets stimulate liver regeneration by local excretion of mitogens stored within platelet granules, definitive evidence for this is lacking, and alternative mechanisms deserve consideration. In-depth knowledge of mechanisms of platelet-mediated liver regeneration may lead to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 62 publications
0
55
0
Order By: Relevance
“…More recently, it was demonstrated that intraoperative platelet count and platelet transfusion were associated with faster liver regeneration in living donor transplant recipients . The molecular mechanisms of platelet‐mediated stimulation of liver regeneration are, however, still largely unknown …”
Section: Introductionmentioning
confidence: 99%
“…More recently, it was demonstrated that intraoperative platelet count and platelet transfusion were associated with faster liver regeneration in living donor transplant recipients . The molecular mechanisms of platelet‐mediated stimulation of liver regeneration are, however, still largely unknown …”
Section: Introductionmentioning
confidence: 99%
“…The decrease of serotonin in Tph1 knockout mice and inhibition of Htr2a and Htr2b, the receptors of serotonin, both impair the process of liver regeneration. The mechanism of serotonin-mediated liver regeneration is still controversial (Lisman and Porte, 2016). On the one hand, serotonin may promote the mitogenic process of hepatocytes in mice after hepatectomy; on the other hand, the decrease in serotonin influences the platelet activation, while the delayed liver regeneration may be a secondary effect of the impaired platelet activation.…”
Section: Serotonin and Tissue Regenerationmentioning
confidence: 99%
“…All the mechanisms promoting liver regeneration and involving platelets are not yet very well understood but they certainly play an important role through the release of various mediators like serotonin, hepatocyte growth factor, insulin growth factor, and vascular endothelial growth factor. The last one supports liver regeneration by stimulating neoangiogenesis [22].…”
Section: Infectious Complicationsmentioning
confidence: 99%